Biochemical characteristics and mineral elements of some Ephedra plant species (Proceedings of the Institute of Biology, 2022)
This study aimed to determine and compare some biochemical characteristics and mineral elements in rare medicinal plants Ephedra equisetina Bunge. and E. przewalskii Stapf. in Mongolia. In 2017, we identified several biochemical characteristics in aerial parts of E. equisetina and E. przewalskii, such as moisture, total ash, protein, lipid, and total carbohydrate, as well as 17 elements.Proteins were determined by the Kjeldahl method, lipid was determined by the Soxhlet method, moisture and total ash were determined by weighing essay, and mineral elements were dissolved in concentrated acids using an inductively coupled plasma optical emission spectrophotometer (ICP-OES).The study’s findings, in particular the moisture content (4.7%), total ash content (13.1%), protein content (7.1%), lipid content (0.83%), total carbohydrate content (20.1%), and elemental content Ca-59.05 mg/g, K-93.7 mg/g, Mg[1]11.3 mg/g, P-13.7 mg/g, and Na-2.24 mg/g are all contained in E. equisetina. E. przewalskii contains the following percentages of moisture: 5.21%, total ash: 11.9%, protein: 7.11%, lipid: 1.2%, total carbohydrate: 15.5%, and element content, particularly Ca: 57.3 mg/g, 24.2 mg/g, Mg: 4.4 mg/g, P: 2.28 mg/g, and Na: 1.69 mg/g. As a result, E. equisetina contained the highest concentrations of ashes and total carbohydrates, whereas E. przewalskii had the highest concentrations of moisture, proteins, and lipids. There was also a significant difference in biochemical characteristics between the two species (p